2017
DOI: 10.12973/eu-jer.6.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Adaptation of the Social Efficacy and Outcome Expectations Scale to Turkish

Abstract: The aim of this study was to examine the psychometric properties of the Social Efficacy and Outcome Expectations Scale (SEOES) on Turkish. The sample group included two groups of university students (ns= 440, 359). The validity of the scale was assessed using exploratory factor analysis, confirmatory factor analysis and concurrent validity, and the reliability was assessed using Cronbach Alpha's internal consistency coefficient, test-retest method and item discrimination. The findings obtained from the explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
2
9
0
3
Order By: Relevance
“…Therefore, they can also effectively cope with the problems they encounter in electronic social environments. Individuals who have established successful social relationships expect similar results in their subsequent social relationship experiences (Bakioğlu, 2020;Bakioglu & Turkum, 2017 ;Wright & Perrone, 2010).…”
Section: Social Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, they can also effectively cope with the problems they encounter in electronic social environments. Individuals who have established successful social relationships expect similar results in their subsequent social relationship experiences (Bakioğlu, 2020;Bakioglu & Turkum, 2017 ;Wright & Perrone, 2010).…”
Section: Social Self-efficacymentioning
confidence: 99%
“…Studies have demonstrated that social self-efficacy is negatively related academic stress, and interpersonal relationship stress (Chiu, 2014), internet addiction (Bakioğlu, 2020;Gazo et al, 2020;Severino & Craparob, 2013), loneliness (Bakioğlu, 2020;Gazo et al, 2020) pathological gambling (Passanisi et al, 2020), game addiction (Jeong & Kim, 2011), online game addiction (Duman & Ozkara, 2019), accepting external influence, and self-alienating (Satici et al, 2013), depression and shyness (Anderson & Betz, 2001). On the other hand, social self-efficacy is positively correlated perceived social support (Adams et al, 2019;Bakioğlu, 2020;Traş & Arslan, 2013), life satisfaction (Bakioglu & Turkum, 2017;Wright & Perrone, 2010), authentic living (Satici et al, 2013), and communication skills and interpersonal problem solving skills (Erözkan, 2013). A negative relationship was found between self-efficacy and FoMO (Erdoğan & Şanlı, 2019;Lee et al, 2020).…”
Section: Social Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Sosyal yeterlik, bireyin sosyal ilişki başlatma ve sürdürmek konusunda becerilerine güvenmesi ve kendisini yeterli görmesidir (Bakioğlu ve Türküm, 2017;Wright, Wright ve Jenkins-Guarnieri, 2013). Sosyal yeterlik bireyin içinde yer aldığı toplumun ve kültürün öğrenilmesi yoluyla gerçekleşmektedir.…”
Section: Introductionunclassified
“…Sosyal yeterlik pek çok kişisel özellikle ilişkili bir alan olarak görülmektedir. Yapılan araştırmalarda, Sosyal yeterlik, yalnızlık (Bakioğlu ve Türküm, 2017;Hermann ve Betz, 2006) ve depresyon (Ahmad, Yasien ve Ahmad, 2014) ile negatif yönde, yaşam doyumu (Bakioğlu ve Türküm, 2017;Wright ve Perrone, 2010), öz saygı (Hermann ve Betz, 2006) ve problem çözme becerileri (Erözkan, 2013) ile pozitif yönde ilişkili bulunmuştur. Ancak sosyal yeterlik kavramının anlaşılması adına daha fazla sayıda araştırma yapılması ve kavram hakkında açıklamaların yapılması gerekli görülmektedir.…”
Section: Introductionunclassified